2018
DOI: 10.1136/bmj.k793
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related adverse events for anti-PD-1 and anti-PD-L1 drugs: systematic review and meta-analysis

Abstract: ObjectiveTo evaluate rates of serious organ specific immune-related adverse events, general adverse events related to immune activation, and adverse events consistent with musculoskeletal problems for anti-programmed cell death 1 (PD-1) drugs overall and compared with control treatments.DesignSystematic review and meta-analysis.Data sourcesMedline, Embase, Cochrane Library, Web of Science, and Scopus searched to 16 March 2017 and combined with data from ClinicalTrials.gov.Study selectionEligible studies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
328
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(357 citation statements)
references
References 46 publications
19
328
3
7
Order By: Relevance
“…Pembrolizumab, an anti‐PD‐1 monoclonal antibody, is approved by the U.S. Food and Drug Administration for the treatment of multiple malignancies, including advanced melanoma, non‐small cell lung cancer, Hodgkin's lymphoma, primary mediastinal B‐cell lymphoma, urothelial carcinoma, and head and neck cancer. Recent meta‐analyses have shown that anti‐PD‐1 drugs are associated with a higher risk of rash when compared with conventional treatment such as chemotherapy or targeted therapy . We present a case of a patient on pembrolizumab who developed diffuse steroid‐refractory lichenoid dermatitis associated with severe pruritus that was successfully treated with a short course of oral cyclosporine.…”
Section: Introductionmentioning
confidence: 99%
“…Pembrolizumab, an anti‐PD‐1 monoclonal antibody, is approved by the U.S. Food and Drug Administration for the treatment of multiple malignancies, including advanced melanoma, non‐small cell lung cancer, Hodgkin's lymphoma, primary mediastinal B‐cell lymphoma, urothelial carcinoma, and head and neck cancer. Recent meta‐analyses have shown that anti‐PD‐1 drugs are associated with a higher risk of rash when compared with conventional treatment such as chemotherapy or targeted therapy . We present a case of a patient on pembrolizumab who developed diffuse steroid‐refractory lichenoid dermatitis associated with severe pruritus that was successfully treated with a short course of oral cyclosporine.…”
Section: Introductionmentioning
confidence: 99%
“…Nivolumab, an anti‐PD‐1 monoclonal antibody, has shown its efficacy in improving survival in patients with metastatic renal cell carcinoma (RCC), and has been approved as a second‐line treatment, after the failure of angiogenesis‐targeted therapy, in this indication. Even though nivolumab has a relatively good tolerance profile, it may induce severe immunologic toxicities that can occur at any time during or even after the treatment, and these side effects are of crucial importance for patient's care . Immune‐related gastrointestinal toxicities are among the most frequently observed and are dominated by colitis, while small intestine toxicities are much less frequent .…”
Section: Introductionmentioning
confidence: 99%
“…Even though nivolumab has a relatively good tolerance profile, it may induce severe immunologic toxicities that can occur at any time during or even after the treatment, and these side effects are of crucial importance for patient's care. [3][4][5][6] Immune-related gastrointestinal toxicities are among the most frequently observed and are dominated by colitis, while small intestine toxicities are much less frequent. 7,8 Only one case of diffuse enteropathy, with immune infiltration extended from the duodenum to the colon, has been reported after a long-term course of nivolumab in a patient with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous data from randomized controlled trials (RCTs) have already shown that PD1/PD‐L1 inhibitor‐related therapeutic regimens are likely to increase the risk of immune‐related pneumonitis, results from these RCTs are not consistent. Traditional systematic reviews and meta‐analyses were conducted to estimate the safety profile of PD1/PD‐L1 inhibitor . However, due to lacking head‐to‐head direct evidence, comparative pneumonitis risk among different PD1/PD‐L1 inhibitor‐related therapeutic regimens have never been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional systematic reviews and meta-analyses were conducted to estimate the safety profile of PD1/ PD-L1 inhibitor. [13][14][15][16] However, due to lacking head-to-head direct evidence, comparative pneumonitis risk among different PD1/PD-L1 inhibitor-related therapeutic regimens have never been systematically studied.…”
Section: Introductionmentioning
confidence: 99%